Relationship between strength qualities and sprinting performance - Young, W.; McLean, B.; Ardagna, J. (The Journal of Sports Medicine and Physical Fitness, 1995)
The purpose of this study was to investigate the relationship between strength measures and sprinting performance, and to determine if these relationships varied for different phases of sprint running. Twenty (11 males and 9 females) elite junior track and field athletes served as subjects. Athletes performed maximum sprints to 50 m from a block start and time to 2.5, 5, 10, 20, 30, 40 and 50 m were recorded by electronic timing gates. The resultant forces applied to the blocks were obtained from two force platforms. Twenty-seven measures of strength and speed-strength (absolute and relative to bodyweight) were collected from the height jumped and the force-time curve recorded from the takeoff phase of vertical jumping movements utilizing pure concentric, stretch shortening cycle (SSC) and isometric muscular contractions. Pearson correlation analysis revealed that the single best predictor of starting performance (2.5 m time) was the peak force (relative to bodyweight) generated during a jump from a 120 degree knee angle (concentric contraction) (r = 0.86, p = 0.0001). The single best correlate of maximum sprinting speed was the force applied at 100 ms (relative to bodyweight) from the start of a loaded jumping action (concentric contraction) (r = 0.80, p = 0.0001). SSC measures and maximum absolute strength were more related to maximum sprinting speed than starting ability. It was concluded that strength qualities were related to sprinting performance and these relationships differed for starting and maximum speed sprinting.